1537 Squamous Cell Carcinoma Arising in A Maxillary Odontogenic Keratocyst in Gorlin Goltz Syndrome - A Rare Case Report. (12th October 2021) - Sarai, R; Raj, S; Parmar, S; Martin, T; Idle, M; Praveen, P; Anstey, H; Hussain, K
Abstract: Introduction: Gorlin Goltz syndrome (GGS) is a rare, hereditary, AD condition with multiple BCCs, odontogenic keratocysts (Jaw cysts), calcification of falx cerebri, skeletal anomalies & a predisposition to neoplasms like medulloblastomas, fibromas and rhabdomyosarcomas. Aim: We present a rare case of a Squamous cell carcinoma (SCC) developing in a Maxillary odontogenic keratocyst in a 32-year male with GGS. Discussion: This patient was referred to the OMFS unit with a non-healing UL3 extraction socket and exophytic growth. Initial biopsies suggested an atypical squamo-proliferative lesion, however a repeat biopsy demonstrated an invasive SCC arising from a background odontogenic keratocyst of the maxilla. He was initially reluctant to undergo a staging CT scan to avoid risks of developing further BCCs due to IR exposure. This was eventually performed as per H&N MDT recommendation & showed a T4aN0M0 SCC of the left maxilla and bilateral multiple mandibular odontogenic keratocysts. He underwent a left maxillectomy, left neck dissection & reconstruction with a DCIA free flap, but did not want his mandibular keratocysts treated at the same time. Complete tumour clearance was achieved with no involved neck nodes & he remains disease-free at 4 months postoperatively. Although for a T4 tumour he would have needed postoperative radiotherapy, in view of the GGS, no adjuvant treatment was indicated. Conclusions: SCC developing in a maxillary OKC is exceedingly rare with only two previous cases reported in GG syndrome. This is the first reported case of a GGS patient with oral SCC undergoing a complex free flap reconstruction.